A Manga Perfeita - Manning, Erin (punctum books, 2019)
"In 1994, at the age of twenty five years old, when the terrible "shattering that comes with the sexual assault "doubled deep into her body and thoughts of suicide were always around, Erin Manning wrote The Perfect Manga on a almost feverish state: nineteen chapters in nineteen days, a kind self-rescue operation where writing has become a way of make (and feel) life in another way. Over these nineteen days, and although not able to fully articulate to herself at the time, Manning was written inside "a composition that asks what otherwise life could be lived. " And in the rhythms of this composition, which was also a life, Manning was and is able to decline the category and norm and immobility of the "victim" (while still understanding the inheritances violence) in order to follow the more-than-myself as well as the joy of "more than experience" Twenty-five years Manning later allows these earlier writings to find their way around the world, which is a way of giving "voice to these confused survival times "while also asking us to we share (and help support) such moments as readers, that we consider "other ways of listening to the urgency of living". Republishing the book now is giving it a place in the world in a way that honor your strength as something that is always beyond the claim of anyone, even from Manning. In this sense, The Perfect Manga invites us, with Manning, to be in excess of ourselves, and also to consider, in Manning's words, "as create conditions for living beyond the fierce belief of humanism that we, the privileged, the neurotypical, the still unscathed, the capable bodies, is that we hold the key to all perspectives in the theater of life ". Finally, Manning Perfect Manga and Manning's reflections on its composition ask us to consider "living in the fierce celebration of a world invented by these ways of life that tear the white, neurotypical colonial fabric of life as the We know.""